Critique of Essentialist Culture in Koirala’s Sumnima - Koirala, Prabal (AJOIS: Academic Journal of Interdisciplinary Studies, 2024)
This paper attempts to analyze how Bishweshwar Prasad Koirala’s novel Sumnima critiques essentialist culture by the rulers of the contemporary time. Presenting two characters from diverse cultural background, Koirala makes a subtle distinction between the culture and way of life. In doing so, he snubs the superiority or inferiority of the cultures and shows that they are unique in their own terms. By taking insights on culture and ethnicity embedded in the identity of a person, this paper reveals that Koirala chides the essentialist thoughts of the rulers.